-(1+7x)-6(-7-x)=36

Simple and best practice solution for -(1+7x)-6(-7-x)=36 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -(1+7x)-6(-7-x)=36 equation:


Simplifying
-1(1 + 7x) + -6(-7 + -1x) = 36
(1 * -1 + 7x * -1) + -6(-7 + -1x) = 36
(-1 + -7x) + -6(-7 + -1x) = 36
-1 + -7x + (-7 * -6 + -1x * -6) = 36
-1 + -7x + (42 + 6x) = 36

Reorder the terms:
-1 + 42 + -7x + 6x = 36

Combine like terms: -1 + 42 = 41
41 + -7x + 6x = 36

Combine like terms: -7x + 6x = -1x
41 + -1x = 36

Solving
41 + -1x = 36

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-41' to each side of the equation.
41 + -41 + -1x = 36 + -41

Combine like terms: 41 + -41 = 0
0 + -1x = 36 + -41
-1x = 36 + -41

Combine like terms: 36 + -41 = -5
-1x = -5

Divide each side by '-1'.
x = 5

Simplifying
x = 5

 

You can always share this solution

See similar equations:

| 3n-5=-8(6+5n) | | 2(4x-3)-8=4+2x | | 5n+34=-2(1-7n) | | -18-6k=6(1+3k) | | -(7-4x)=9 | | 14=-(p-8) | | 12=-4(-6x-3) | | -8=-(x+4) | | p-4=-9+p | | 6x-y=7 | | s=2g+2v | | n=wsz | | 3x+12-5x=22 | | a+(a-4)=(a+5)-(a+1) | | 0.7(9x+5)=0.6-(x-3) | | -15=-6+3y | | 2.4x+48.1=2.2-12.9x | | 66-(3x+11)=3(x+9)+x | | -4+2x=8 | | 3y-7+y+25=7y+20-5y | | 8+19t-4=6t+36-3t | | (x-5)(4x+1)=0 | | 3(y+7)=3(y-4) | | 3(3+3x)-2=34 | | 19=3y+4 | | 4(3x-2)=40 | | 9x-42=3x | | 9d=d+8d | | -5=5+5x | | 6.5+1.8n=2.54 | | 6.5+1.8n=1.82 | | 2w-7=-17 | | 4.6+1.7n=1.03 | | 20-x=7 | | 5+5x=25 | | -58=5+7x | | (3k-1)(k+4)=11 | | 9x-18=27 | | x-7y=28 | | 22=x-9 | | X=21+8x | | 13-(r+5)=4(r+7) | | X+5-8x=26 | | 22=y-6 | | v+7=23 | | (12-z)z= | | 4(x-b)=x | | a=bxt+c | | 5(r+3)=2r+6 | | 9-6x=-39 | | 3v+8=8+2v+v | | 6x=9.6 | | 6-3d=5(2-d) | | (4-n)2.1-4.3n=15 | | 5(b+4)-6b=-24 | | 2(8+4c)=32 | | 5x+7=-7x+19 | | 13-3d=-8 | | -23=-2a-10+8 | | 3+a-2=4-2a | | 9+-6-6t=6 | | -w+4(w+3)=-12 | | -2z-xy=x+7 | | 3(2x-3)=7-x | | 3-4x+4=6-5x-2 |

Equations solver categories